An unexpected parasitic cause of hypereosinophilia: fascioliasis - Gökçe, Müge; Sahiner, Umit; Unal, Sule; Parlakay, Aslinur; Oncel, Ibrahim; Saçkesen, Cansin; Kara, Ateş; Gümrük, Fatma (The Turkish Journal of Pediatrics, 2011)
A six-year-old boy from Eastern Anatolia was admitted to our outpatient clinic with abdominal pain and hyperleukocytosis. His leukocyte count was 50 x 10(9)/L with an 80% eosinophilia. Serological investigation was positive at a titration of 1/2560 for Fasciola hepatica. Hepatomegaly with linear hypoechogenic strains, which is typical for F. hepatica, was seen on abdominal ultrasonography. He was successfully treated with triclabendazole, 10 mg/kg/day. He is now under follow-up without any complaints. Hypereosinophilia mimicking leukemia is not an expected finding. To our best knowledge, high leukocyte count with F. hepatica in a child has not been reported in the literature until now.